Atom-Economical C2 + N1 Aziridination: Progress towards Catalytic Intermolecular Reactions Using Alkenes and Aryl Azides - Jenkins, David M. (Synlett, 2012)
The direct synthesis of aziridines from alkenes and a nitrene source with the correct functionality on the nitrogen atom has remained an elusive goal in synthetic chemistry. Ruthenium, cobalt, and iron porphyrin complexes have been demonstrated to catalyze the formation of aziridines from electron-withdrawing aryl azides and a limited selection of conjugated alkenes. Our group is expanding the scope of catalytic aziridination to include electron-donating aryl azides and aliphatic alkenes through the use of a novel tetracarbene iron catalyst.
Keywords: azides; alkenes; catalysis; aziridination; transition metals